Strategy recommendations for policy makers initiatives in South-South cooperation : transferring the Jamaica Customs Automated Services (CASE) solution to the Antigua and Barbuda Customs and Excise Division (IDRC WashingtonUS, 2009)
Focuses on the introduction of CASE and the benefits that were derived from its implementation in Jamaica and Antigua and Barbuda. Presents a synopsis of the findings of CASE and focuses on the key areas of implementation and achievements. Elaborates more generally on those areas to be avoided.
Bibliography: p. 41-42